Budd-Chiari syndrome: long term success via hepatic decompression using transjugular intrahepatic porto-systemic shunt - Zahn, Alexandra; Gotthardt, Daniel; Weiss, Karl Heinz; Richter, Götz Martin; Schmidt, Jan; Stremmel, Wolfgang; Sauer, Peter (BMC gastroenterology, 2010)
Budd-Chiari syndrome (BCS) generally implies thrombosis of the hepatic veins and/or the intrahepatic or suprahepatic inferior vena cava. Treatment depends on the underlying cause, the anatomic location, the extent of the thrombotic process and the functional capacity of the liver. It can be divided into medical treatment including anticoagulation and thrombolysis, radiological procedures such as angioplasty and transjugular intrahepatic porto-systemic shunt (TIPS) and surgical interventions including orthotopic liver transplantation (OLT). Controlled trials or reports on larger cohorts are limited due to rare disease frequency. The aim of this study was to report our single centre long term results of patients with BCS receiving one of three treatment options i.e. medication only, TIPS or OLT on an individually based decision of our local expert group.